D Pengaruh Model Pembelajaran Discovery Learning Terhadap Reduksi Miskonsepsi Siswa Pada Materi Energi Terbarukan - Siregar, Ermila Sari; Hutahaean, Juniar; Napitupulu, Nurasyah Dewi (Universitas Pendidikan Mandalika, 2025)
This study aims to determine the effect of the discovery learning model on reducing students' misconceptions about renewable energy. The research design is a quasi-experimental design with two sample classes selected using cluster random sampling, namely class X-2 as the experimental class and X-3 as the control class. The instrument used was a five-tier diagnostic test consisting of 20 questions that had been validated by validators and pilot-tested on students. The results showed that the average misconception rate among students in the experimental class before the intervention was 44.33%, and after the intervention, the average misconception rate was 24.53%. Thus, there was a 19.8% decrease in misconceptions in the experimental class. Meanwhile, in the control class, the average misconception rate of students before the treatment was 42.33%, and after the treatment, the average misconception rate of students was 31.17%, resulting in an 11.6% decrease in misconceptions. Based on the results of the one-tailed t-test on the posttest data, the tvalue was 12.0196, which was far greater than the ttable value of 2.000, so Ha was accepted. This shows that the discovery learning model has a significant effect in reducing misconceptions in renewable energy material compared to conventional learning.